Analisis Faktor Pendorong dan Kualitas Pelayanan Transportasi Pengiriman Barang Door to door Berbasis Aplikasi mySPIL - Dwi Laraswati Astriawati; Ningrum Astriawati; Iswanto (JURNAL TRANSMA, 2026)
Indonesia, as an archipelagic country, faces geographical challenges that require the implementation of an integrated multimodal transportation and logistics system. Maritime transportation plays a strategic role as the backbone of inter-island goods distribution, which must be supported by land transportation in providing door-to-door delivery services. This study aims to analyze the driving factors and service quality of door-to-door freight transportation based on the digital application mySPIL at PT. Salam Pacific Indonesia Lines (SPIL) Pontianak Branch. The research employs a qualitative approach using field observations, interviews, and documentation studies. The research data consist of primary data obtained from operational staff and outport monitoring staff of PT. SPIL, as well as service users, and secondary data in the form of company documents, cost tables, and other supporting information. The results indicate that PT. SPIL’s door-to-door freight delivery services are supported by the integration of maritime and land transportation modes, structured inbound and outbound operational systems, and the utilization of the mySPIL application as a digital platform for booking, document management, shipment tracking, and real-time payment. The main driving factors for service effectiveness include appropriate shipping capability, the availability of competitive transportation services, consistent service quality, and transparent information provided to customers.